2011
DOI: 10.1246/cl.2012.95
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Preparative Method of Silica Nanotubes by Utilizing Self-assembly and Disassembly of Peptide Amphiphiles

Abstract: The addition of 2,2,2-trifluoroethanol (TFE) induces both the transition from β-sheet to α-helix structure of peptides and disassembly of wormlike micelles of peptide amphiphiles. The hierarchical structural changes were utilized for the preparation of silica nanotubes from silica-micelle complexes with avoiding structural deterioration that is normally caused by thermal treatment. This method is advantageous for the preparation of silica nanotubes because of reusability of peptide templates, possible replicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Assembly and disassembly of another (PA)-system, where the (PA) self-assembled into worm-like micelles, was demonstrated to be useful in the preparation of silica nanotubes. 27,28 However, even though the studies with (PA) shed light on the formation and morphology of 1D structures, our study differs from them in the sense that our peptide has no surface-active behavior.…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…Assembly and disassembly of another (PA)-system, where the (PA) self-assembled into worm-like micelles, was demonstrated to be useful in the preparation of silica nanotubes. 27,28 However, even though the studies with (PA) shed light on the formation and morphology of 1D structures, our study differs from them in the sense that our peptide has no surface-active behavior.…”
Section: Introductionmentioning
confidence: 75%
“…Single molecules which have a radius of gyration of $0.44 nm (ref. 28) are below the cryoTEM detection limit. Surprisingly, under these conditions sheet-like fragments were observed already after 15 min, and in this case no fibrous aggregates were observed (Fig.…”
Section: Nanotube Formation After Temperature Assisted Dissolutionmentioning
confidence: 94%
“…Peptide surfactants can self-assemble into micelles, vesicles and a wide array of high-aspect-ratio nanostructures, such as nanobers, nanotapes, helical ribbons and tubules, with specic biological applications. [11][12][13][14][15][16][17][18][19][20] These attractive features of peptide surfactants are inherently related to hydrogen bonding between peptide sequences and hydrophobic interactions between alkyl chains. Therefore, variations in these factors can dramatically affect the aggregation behavior of peptide surfactants.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a number of strategies to design self-assembled organic aggregates has been developed in order to make these organic matrices work as templates/scaffolds/catalysts for a deposition of silica at ambient conditions [ 20 ]. Recently, self-assembled fibrils of polypeptides [ 21 29 ] or amine-modified polysaccharides [ 30 ] have been used as template for the formation of silica nanotubes. For example, Yuwono et al [ 23 ] reported the use of peptide-amphiphile nanofiber templates in order to direct the synthesis of hollow silica nanotubes with outer diameters of 15–23 nm.…”
Section: Introductionmentioning
confidence: 99%